(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Michael Jackson was a man who made a discourse of his own. He was that dream star whom everyone desired to be. Even though claimed to be an open book, years of trauma and pain lay buried in his unconscious. He experienced a hollowness while being whole. He was a victim of childhood trauma. In order to overcome this trauma the mind develops syndromes. A syndrome is a collection of symptoms that is experienced by some kind of social pattern. The symptoms associated with Michael was that of Peter Pan. One will never forget the effeminate boy Peter Pan, in Never Never Land, who never grew up. This paper is an attempt to analyse Michael Jackson’s life as an escapade from his childhood trauma along the lines of Peter Pan Syndrome.